Preliminary evaluation of a brief mindfulness-based stress reduction intervention for mental health professionals. (February 2016) - Dobie, Alana; Tucker, Alison; Ferrari, Madeleine; Rogers, Jeffrey M
Objectives: Mental health professionals are particularly susceptible to occupational stress; however, there are limited formal programmes to address the problem. This paper discusses the preliminary results of a brief mindfulness-based stress reduction (MBSR) programme for practising professionals in a public hospital mental health unit. Method: A mixed-group of nine mental health professionals participated in eight weeks of daily 15-minute MBSR training interspersed with three 30-minute education sessions developed by the authors (AD and AT). Levels of psychological distress and mindfulness skill were measured before and immediately after participation. Results: Following the brief MBSR programme, quantitative and qualitative participant feedback revealed a perceived reduction in psychological distress. Conclusions: A brief MBSR programme can be incorporated into the full-time workloads of practicing mental health professionals, potentially addressing a significant unmet workplace need.